Aspectos epidemiológicos da leishmaniose visceral em Sergipe e liberação de redes extracelulares de neutrófilos em cães e humanos na infecção por Leishmania infantum - Campos, Roseane Nunes de Santana (2016)
Visceral Leishmaniasis (VL) is a serious infectious disease and is increasing geographical expansion and urbanization. patterns of transmission of the disease are altered due to human actions. The dog is considered the main reservoir of the parasite. The development of the disease depends in part on the host immune system. Neutrophils are considered the first line of defense against pathogens and important agents in the control of LV. These cells have an additional mechanism to eliminate microorganisms that occur with the release of extracellular networks (Neutrophil Extracellular Traps -NETs). This work has two overall objectives, the first being an epidemiological study of LV in Sergipe and the second evaluation of NETs formation in human neutrophils and dogs with LV stimulated with L. infantum, so this thesis was divided into chapters, for better understanding. Epidemiological evaluation were used SINAN data and serosurveys canines Zoonosis Aracaju-SE. A descriptive analysis of the data and construction of distribution maps of disease was performed. Sergipe Aracaju and from 2008 to 2014 the incidence rate in humans with LV increased and the percentage of infected dogs has doubled in the capital. The percentage of cases positive for human VL by sex, according to the age of the patient group, showed that over 15 years the disease affects more males. The spatial distribution analysis allowed to view areas of the city with the highest concentration of human and canine VL. The neighborhoods located in poor areas or growing areas were those with the highest incidence of the disease in humans and dogs. The results show that presents endemicity for human and canine VL. In order to evaluate the formation of NETs were used human groups: Control; LV treated and positive DTH. The dogs were divided into control; Asymptomatic and symptomatic. Neutrophils were isolated from patients with LV University Hospital / UFS and dogs diagnosed with VT by Zoonoses were incubated with and without stimulation of parasite and NETs measures in the supernatant of the cultures after 90 minutes. The parasitic load determined after 24 and 48 hours of interaction with neutrophils treated by the limiting dilution technique. In the evaluation of NETs induction of human neutrophils and release dogs with LV greater amount of NETs when stimulated with L. infantum. When compared between the groups individuals positive DTH release fewer NETs stimulated or not with the parasite. At 24 and 48 hours LV treated subjects have a higher parasite load and showed positive DTH fewer parasite than the other groups tested. Dogs with LV release signals greater amount of NETs when stimulated with L. infantum and have higher parasitic load after 48 hours. It is observed that the release of NETs and control of parasitic load by neutrophils varies according to the clinical form of the LV, in humans and dogs.